2007
DOI: 10.1029/2006jd007791
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the shortwave radiative budget to the parameterization of ice crystal effective radius

Abstract: [1] A new effective particle size (R eff ) parameterization for ice clouds has been formulated based on depth into cloud relative to cloud top. This parameterization has been developed based on an extensive data set of lidar and radar ice cloud retrievals. Using this parameterization within the stand-alone radiation code from the European Centre for Medium Range Weather Forecasting (cy23r4), the performance of the new parameterization is compared with the more commonly used parameterizations based on temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…2.1.3. The CLH was used in the 2002 CRYSTAL-FACE (Jensen et al, 2004), the 2004 Midlatitude Cirrus Experiment (Mid-CiX), the 2006 Tropical Composition, Cloud, and Climate Coupling mission (TC4, Toon et al, 2010), and the 2008 Stratosphere-Troposphere Analyses of Regional Transport (START08) campaign (Pan et al, 2010). The IWC measurements from these campaigns were taken primarily in the midlatitudes and the northern tropics.…”
Section: Clh Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1.3. The CLH was used in the 2002 CRYSTAL-FACE (Jensen et al, 2004), the 2004 Midlatitude Cirrus Experiment (Mid-CiX), the 2006 Tropical Composition, Cloud, and Climate Coupling mission (TC4, Toon et al, 2010), and the 2008 Stratosphere-Troposphere Analyses of Regional Transport (START08) campaign (Pan et al, 2010). The IWC measurements from these campaigns were taken primarily in the midlatitudes and the northern tropics.…”
Section: Clh Instrumentmentioning
confidence: 99%
“…Therefore, they are able to produce either a warming or a cooling effect on the Earth, depending on the balance between these two processes. The microphysical properties of an individual cirrus cloud, such as the cloud particle sizes (Liou et al, 2008) and the crystal habits (van Zadelhoff et al, 2007), contribute to whether absorption or reflection will dominate for a particular cloud. Determining the exact role of cirrus in the radiation budget of the atmosphere is difficult, however, owing to the assortment and variability of the microphysical, and thus radiative, properties involved, as well as the current lack of understanding of how and why some of those variations occur.…”
Section: Introductionmentioning
confidence: 99%
“…RACMO2.1 is used extensively for regional climate downscaling (e.g., Lenderink et al 2007) and evaluating of various components of the physical parameterization (e.g., Van Zadelhoff et al 2007). The simulation used in the present study is a regional downscaling experiment focusing on the West African monsoon area applied in the context of the European Commission-sponsored project ENSEMBLES (Hewitt and Griggs 2004).…”
Section: Set Up and Brief Verification Of The Regcmmentioning
confidence: 99%
“…The difference can be as large as 32 W m 22 on the daily time scale and 4 W m 22 on the seasonal scale according to Iacoellis et al (2003). Van Zadelhoff et al (2007) showed that observation-model difference in terms of radiation flux is reduced from as large as 15 W m 22 with an old scheme to 0.7 W m 22 using a new parameterization of ice particle sizes (Donovan 2003). They also reported significant changes of yearly average albedo in the model due to parameterization alone.…”
Section: Introductionmentioning
confidence: 99%